Year of the patent [intellectual property protection, China]. - Frank, S.J (IEEE spectrum)
Protecting intellectual property isn't China's strong suit, but the country is trying to tailor its IP laws to assuage foreign companies. How far the country goes in establishing an enforceable intellectual property (IP) regime will affect the nation's economic fortunes, and also will likely determine its ability to make technology a component of its future growth. Without the ability to protect innovations systematically and to use those protections to stake out markets and combat piracy, no firm can hope to compete profitably. Savvy technology companies refuse to play in countries where the deck is stacked. To satisfy WTO standards and address international criticism, China amended its patent laws in July 2001 so that even offers to sell a pirated product (in addition to actual sales) constitute acts of infringement. The new laws allow judicial appeal of adverse decisions in reexamination and invalidation procedures; permit preliminary injunctions before infringement actions are even heard; and make compulsory licensing-that is, forcing a patent owner to license the technology to others-more difficult. But what remains to be seen is how these changes affect matters "on the ground"-whether what looks good on paper actually heralds a new willingness to protect IP rights.